Comparative Analysis of Aluminum Formwork and Conventional Formwork on the Success of the Structural Work Quality - Yehezkiel Rivaldo; I Nyoman Dita Pahang Putra (Nusantara Journal of Multidisciplinary Science, 2024)
Formwork innovations in the world of construction continue to develop, one of which is aluminum formwork. It was found that there were differences in the quality of work on aluminum and conventional formwork structures, so it was necessary to carry out an analysis regarding this matter. The method used is to analyze the results of questionnaires and expert interviews. The analysis carried out aims to determine the results of work on aluminum and conventional formwork structures on the success of structural work and the differences using a multiple linear regression model. The results of the research show that the influence of the results of aluminum and conventional formwork structures on the level of success of the quality of structural work on the Kediri Regency Stadium construction project can be identified through the regression equation Y = 3.946 + 0.564 X1 + 0.392 X2 + 0.155 with an Adjusted R Square value of 0.949. This means that the more aluminum formwork structural work results, the more successful the quality of the structural work will be. Apart from that, there is a difference in the quality of structural work between aluminum and conventional formwork on the Kediri Regency Stadium construction project with an average difference in acceptance of 5.08%. Based on parameters, the quality of work on aluminum formwork structures is superior to the quality of work on conventional formwork structures.